Tunneling of massive vector particles from types of BTZ-like black holes - Javed, Wajiha; Ali, Riasat; Babar, Rimsha; Övgün, Ali (Springer Heidelberg, 2019)
.In this paper, we analyze the Hawking radiation phenomenon for types of Banados-Teitelboim-Zanelli-like (BTZ-like) black holes. For this purpose, using the Hamilton-Jacobi method, we consider semi-classical WKB approximation to calculate the tunneling probabilities of massive boson particles. For these particles, we use the equation of motion for the Glashow-Weinberg-Salam model. Using the quantum tunneling process of charged massive bossons, we compute the corresponding Hawking temperatures. Furthermore, we discuss the effects of the rotation parameter on the tunneling probability and temperature.
Keywords: Hawking Radiation; Kerr